Development and Evolution of Indonesian Law from the Perspective of Development Law Theory - Risnandar, Aep; Zaenudin, KM Ibnu Shina (Rechtsvinding, 2025)
This research examines the development of Indonesian law from the perspective of the Theory of Development Law proposed by Mochtar Kusumaatmadja, emphasizing the role of law as a proactive agent in social transformation. Using a normative-juridical approach, the analysis focuses on strategic regulations such as the Investment Law and the Job Creation Law, which, despite aiming to boost economic growth, still fail to fundamentally address social inequality. This paper also explores the challenges of the digital age, particularly digital inclusion, data protection, and algorithmic fairness, which are becoming increasingly crucial in legal systems. The research results indicate that the current development of Indonesian law is more focused on economic growth, but is not yet effective enough in addressing social and economic inequality. The law needs to be reformed to be more just and inclusive, providing real protection for marginalized groups, and developing law theory must adapt to the digital era and the data economy. Digital regulation is important for data protection and inclusion, as well as leveraging technology to ensure justice and equitable access in technology-based development. These findings propose more inclusive and just legal reforms, focusing on strengthening legal institutions and culture to protect marginalized groups and ensure equal and transparent legal access for all members of society, and digital regulations must be developed to guarantee the protection of personal data, digital inclusion, and transparency using the latest technologies, so that the benefits of digital transformation can be felt equally without creating new disparities.